Expression of the domain cassette 8 Plasmodium falciparum erythrocyte membrane protein 1 is associated with cerebral malaria in Benin. - Gwladys I Bertin (Public Library of Science (PLoS), 2013)
Background Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP-1) is a highly polymorphic adherence receptor expressed on the surface of infected erythrocytes. Based on sequence homology PfEMP-1 variants have been grouped into three major groups A-C, the highly conserved VAR2CSA variants, and semi-conserved types defined by tandem runs of specific domains ("domain cassettes" (DC)). The PfEMP-1 type expressed determines the adherence phenotype, and is associated with clinical outcome of infection. Methods Parasite isolates from Beninese children or women presenting with, respectively, CM or PAM were collected along with samples from patients with uncomplicated malaria (UM). We assessed the transcript level of var genes by RT-qPCR and the expression of PfEMP-1 proteins by LC-MS/MS. Results Var genes encoding DC8 and Group A PfEMP-1 were transcribed more often and at higher levels in cerebral malaria vs. uncomplicated malaria patients. LC-MS/MS identified peptides from group A, DC8 PfEMP-1 more frequently in cerebral malaria than in uncomplicated malaria and pregnancy-associated malaria samples. Conclusion This is the first study to show association between PfEMP-1 subtype and disease outcome by direct analysis of parasites proteome. The results corroborate that group A and specifically the PfEMP-1 types DC8 are universally associated with cerebral malaria. This is a crucial observation for promoting studies on malaria pathogenesis.